Persepsi Guru Pendidikan Jasmani Pada Pembelajaran Pendidikan Jasmani Pada Masa Pembelajaran Tatap Muka Terbatas di SMP/MTs Se-Kecamatan Kotabaru - Reza Abdul Rozak; Ruslan Gani; Fahrudin Fahrudin (Peneliti.net, 2022)
This research is motivated by the perception of physical education teachers on physical education learning during the limited face-to-face learning period in SMP/MTs in Kotabaru District. This study was to determine the perception of physical education teachers on physical education learning during the limited face-to-face learning period in SMP/MTs in Kotabaru District, researchers conducted indicators, such as functional factors including clarifying the material presented, facilitating learning, delivering material systematically and logically. , Increase the ability to understand the material, and Improve achievement. While structural factors Streamlining the learning process, Using time efficiently. This research is a descriptive survey research. The population is 23 people. The sample taken in this study is the total population. The instrument used is a closed questionnaire with five score answers using a Likert Scale. The results of the study as a whole show that the perception of physical education teachers on physical education learning during the face-to-face learning period is limited in SMP/MTs in Kotabaru District in the low category with a percentage of 61.16%.